Seizure Duration and Spread Dynamics in MRI-Defined Subtypes of Temporal Lobe Epilepsy. (26th July 2022) - Zhang, Victor Jia Wei; Jackson, Graeme D.; Fitt, Gregory; Perchyonok, Yuliya; Vaughan, David Noel
Abstract : Background and Objectives: MRI and PET imaging enables subgroups of temporal lobe epilepsy (TLE) to be defined on the basis of structural pathology. Few studies have examined the variation in electroclinical seizure spread patterns based on imaging findings. We performed a retrospective cohort study to investigate the electroclinical differences among 3 specific groups of TLE: MRI-negative PET-positive TLE (MRI-negative TLE), temporal lobe lesion TLE (lesional TLE), and unilateral hippocampal sclerosis TLE (HS-TLE). Methods: Patients with an electroclinical diagnosis of TLE who had video-scalp EEG recordings of seizures were identified from the retrospective database of the Austin Comprehensive Epilepsy Program between 2005 and 2019. The cohort was further selected into the 3 defined groups based on imaging findings, using MRI and FDG-PET. Timings of clinical and electrographic seizure progression were measured, considering the onset, ipsilateral lobar spread, contralateral spread, and termination. Durations were compared between groups using linear mixed models with inclusion of demographic and clinical covariates. Results: A total of 105 patients (137 seizures) were included, comprising 36 with MRI-negative TLE (54 seizures), 36 with lesional TLE (18 lateral vs 16 mesial lesions; 44 seizures), and 33 with HS-TLE (39 seizures). Seizure duration was similar between MRI-negative TLE and lesional TLE (mean 75.9 vs 71.7 seconds; p = 0.91). Further dividing lesional TLE into medial vs lateral temporal revealed no timing difference. However, the HS-TLE group had longer total seizure duration (114 seconds) compared with both MRI-negative TLE ( p < 0.001) and lesional TLE ( p < 0.001). Progression of electrographic spread also reflected this pattern, with involvement of extratemporal regions and then the contralateral hemisphere each taking significantly longer in HS-TLE. Discussion: MRI-negative TLE appears electrographically similar to lesional TLE, whether mesial or lateral, in the duration of seizures and the timing of electrographic spread. Both appear electrographically different from HS-TLE, where propagation is slower, suggesting engagement of different epileptogenic networks or seizure suppression mechanisms. Classification of Evidence: This study provides Class II evidence that the electroclinical features of seizures in HS-TLE are different than MRI-negative TLE and lesional TLE.